Über Moore und Torf auf Madagaskar und den Maskarenen - Straka, Herbert (ERDKUNDE, 1960)
This work summarizes the results of surveys in the bogs of Madagascar and the Mascarene Islands. It first gives a brief overview of the geology and vegetation of the islands. Since determinations of most plant species in the dry season, during which the surveys had to be conducted, were not possible, I helped to search the bibliography on the vegetation of the peat bogs in the regions visited. This vegetation is relatively uniform throughout the island of Madagascar. One can distinguish peat bogs with Sphaignes, Ferns and Cyperaceae, and floating bogs. These types are found in Reunion, and Pandanus swamps and S tillin gia and Croton swamps have been described in Mauritius. Boreholes in the central highlands of Madagascar have yielded in swampy volcanic craters or in marshes of filled lakes, blocked by lava flows, profiles up to 10.5 m deep. Spring bogs and swampy lowlands have yielded only 2.60 m of peat at most. In the depression of Lake Alaotra, only thin layers of peat were found. In the ombrophilous forest of the eastern area, a profile of 3.20 m. of depth was probed, in the coastal region up to 3.70 m. of peat. The West and South of Madagascar are poor in bogs. Only once was 1.20 m. of bend found. In the Mare à Joncs in Reunion I touched after a layer of peat of 3.55 m. the volcanic tuff. In Mauritius there was Au Petrin 1,90 m. of peat and Au Bouton perhaps important layers of peaty substance. The bogs visited are mostly topogenous. The planned polar analyses require preparatory work on the morphology of the pollen grains. Radiocarbon (C14) research was also considered.